Ethyl glucuronide concentration in serum of human volunteers, teetotalers, and suspected drinking drivers - Schmitt, Georg; Drönner, Peter; Skopp, Gisela; Aderjan, Rolf (Journal of forensic sciences, 1997)
The kinetic profile of ethanol and ethyl glucuronide (EtG) in serum was investigated in three subject groups: 1) Healthy, moderately drinking volunteers (daily intake less than 30 g ethanol) who ingested a single dose of ethanol. In this group the maximum of serum ethyl glucuronide concentration (SEtGC) and of serum ethanol concentration (SEC) did not exceed 3.7 mg/L and 1.5 g/L respectively. EtG peaked 2 to 3.5 h later than ethanol. EtG was eliminated with a terminal half-life of 2 to 3 h. EtG decreased slower than ethanol—the metabolite could still be determined in serum up to 8 h after complete ethanol elimination. 2) In serum samples of teetotalers neither ethanol nor EtG could be found. 3) In 37 of 50 serum samples of drivers suspected of driving under the influence of ethanol, SEtGC was found between the limit of detection (0.1 mg/L) and 20 mg/L. If the SEC is less than 1 g/L and the SEtGC is significantly higher than 5 mg/L, we assume alcohol misuse.